2014
DOI: 10.1002/btpr.1930
|View full text |Cite
|
Sign up to set email alerts
|

The bioactivity and fractionation of peptide hydrolysates in cultures of CHO cells

Abstract: Peptide hydrolysate supplements in mammalian cell cultures provide enhanced growth and productivity. The objective of this study was to compare the bioactivity of ten different commercially available hydrolysates from plant, microbial, and animal sources. The peptide hydrolysates were tested as supplements to cultures of Chinese hamster ovary (CHO) cells that produce human beta interferon (β-IFN). A soy hydrolysate was shown to support high cell growth but not protein productivity compared to an animal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…The use of an alternative, more specific agent that could be more readily incorporated into an industrial bioprocess and at lower concentrations is preferable. Indeed, current media formulations often contain peptides as part of hydrolysates added to the medium to increase growth and productivity (Spearman et al, 2014). This made the use of a unique and specific cell‐permeable, autophagy‐inducing peptide (AIP), derived from the autophagy protein Beclin 1 (Shoji‐Kawata et al, 2013), suitable for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an alternative, more specific agent that could be more readily incorporated into an industrial bioprocess and at lower concentrations is preferable. Indeed, current media formulations often contain peptides as part of hydrolysates added to the medium to increase growth and productivity (Spearman et al, 2014). This made the use of a unique and specific cell‐permeable, autophagy‐inducing peptide (AIP), derived from the autophagy protein Beclin 1 (Shoji‐Kawata et al, 2013), suitable for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, model-based approaches were used to identify a putative autocrine factor that influences the growth and death rates of various hybridoma cell lines in continuous and perfusion culture (Zeng, 1996;Zeng & Deckwer, 1999). Recent studies mainly focused on the effects of lowmolecular weight peptides (1-10 kDa) from hydrolysates on the growth and productivity of mammalian cell culture (Chabanon et al, 2008;Franěk & Fussenegger, 2005;Michiels et al, 2011;Spearman, Lodewyks, Richmond, & Butler, 2014). To the authors' knowledge, the chemical structure, its formation, mechanism of action, and degradation of putative autocrine factors are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In CHO cells, Spearman et al . ( 2014 ) showed that soy hydrolysate promotes cell growth but did not increase protein productivity; while yeast hydrolysate reduces cell growth, but achieved a comparable level of protein productivity and glycosylation profile as an animal-based hydrolysate. This suggests that yeast hydrolysate would be a good alternative to animal-based hydrolysate if the quality of the protein produced is the most important attribute.…”
Section: The Use Of Hydrolysate In Animal Cell Culturementioning
confidence: 99%
“…In a more recent study, cottonseed-derived hydrolysate enhances the galactosylation of CHO-S-RTX and CHO-EG2 cells, which in turn improves the product quality (Obaidi et al 2021 ). Furthermore, the glycosylation profile of the protein produced by CHO cells is equivalent between yeast and animal-based hydrolysate (Spearman et al 2014 ). This study demonstrated that biopharmaceutical manufacturers should consider the use of yeast hydrolysates to improve protein productivity and glycosylation of the product.…”
Section: The Use Of Hydrolysate In Animal Cell Culturementioning
confidence: 99%